2013
DOI: 10.3109/10409238.2013.838205
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation by hypoxia inducible factors

Abstract: The cellular response to oxygen deprivation is governed largely by a family of transcription factors known as Hypoxia Inducible Factors (HIFs). This review focuses on the molecular mechanisms by which HIFs regulate the transcriptional apparatus to enable the cellular and organismal response to hypoxia. We discuss here how the various HIF polypeptides, their post-translational modifications, binding partners and transcriptional cofactors affect RNA polymerase II activity to drive context-dependent transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
555
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 640 publications
(579 citation statements)
references
References 177 publications
20
555
0
4
Order By: Relevance
“…24 Since tumor VN is also characterized by a loss of hypoxia (and a return to normoxia) within the TME, 24,25 we analyzed treated vs. control tumors for expression of the hypoxiaassociated biomarker HIF-2a. [25][26][27] We determined that tumors in mice vaccinated with lvDLK1 or (more so) lvDLK1 C lvDLK2 displayed significant reductions in HIF-2a transcript levels vs. control-untreated tumors (Fig. 3D), consistent with therapeutic VN in these treatment cohorts.…”
Section: Resultssupporting
confidence: 51%
“…24 Since tumor VN is also characterized by a loss of hypoxia (and a return to normoxia) within the TME, 24,25 we analyzed treated vs. control tumors for expression of the hypoxiaassociated biomarker HIF-2a. [25][26][27] We determined that tumors in mice vaccinated with lvDLK1 or (more so) lvDLK1 C lvDLK2 displayed significant reductions in HIF-2a transcript levels vs. control-untreated tumors (Fig. 3D), consistent with therapeutic VN in these treatment cohorts.…”
Section: Resultssupporting
confidence: 51%
“…In addition to oxygen-dependent stabilization of HIF-1α, HIF-1 is also controlled by mechanisms not directly involving oxygen but implicating oncogenic signaling pathways, protein interactions and diverse modifications (Dengler et al, 2014). Direct phosphorylation by kinases such as GSK3, PLK3, CDK1 and ATM (Kietzmann et al, 2016) affect HIF-1α protein stability, whereas others, such as ERK1 and ERK2 (ERK1/2, also known as MAPK3 and MAPK1, respectively; hereafter referred to as ERK) (Mylonis et al, 2008) and CK1δ (CSNK1D) (Kalousi et al, 2010), control its activity by affecting nuclear accumulation or heterodimerization with ARNT, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of HIF1α and HIF2α subunits has been demonstrated to enhance transactivation of target genes by either disrupting interaction with VHL and thereby stabilizing HIFs, or by increasing the affinity of HIFs for transcriptional coactivators [13]. In this regard, it has been reported that casein kinase II phosphorylates both HIF1α and HIF2α at conserved theonine residues in their C-TADs and that the mutation of these residues diminished their activity [48,49].…”
Section: Genes Regulated By Hif Alpha Subunitsmentioning
confidence: 99%
“…Comparatively, the bHLH and PAS domains of HIF3α share only 74% and 52-58% identity with HIF1α and HIF2α, respectively, revealing a more divergent nature of this paralog [13].…”
Section: Protein Structure Of the Oxygen-labile Alpha Subunitsmentioning
confidence: 99%
See 1 more Smart Citation